Influence of Brand Loyalty, Brand Image and Brand Equity on Attendance Intention in Three Private Universities in Peru: A Quantitative Case Study - Yessica ERAZO-ORDOÑEZ; Elizabeth Emperatriz GARCÍA-SALIRROSAS; Roberto MACHA-HUAMÁN (Communications of International Proceedings, 2024)
Higher education services in Peru face increasing competition in attracting and retaining students. Understanding which elements lead students to choose one university over another is fundamental for universities to develop more effective marketing strategies. This study, based on a quantitative approach, seeks to offer a clearer vision of the components that influence the decisions of prospective students, allowing universities to formulate policies and practices that strengthen their image and, therefore, their competitiveness in the educational market. There are several studies on the variables in the business context, however there is a scarcity of research in the educational sector, therein lies the knowledge gap. The objective of this study is to analyze to what extent loyalty, brand image and brand value influence the intention to attend private universities in Peru.  The study has a quantitative approach, with a non-experimental cross-sectional design and an explanatory level with the use of structural equations. The study sample consisted of 381 students from 3 private universities in the capital of Peru. The results of the theoretical model were accepted because the RMSEA and SRMR values are very close to zero, the CFI =0.974, Chi-square (X^2)= 268 and (df)=144. It was found that brand loyalty influences attendance intention (β=0.39), brand value influences attendance intention (β=0.24) and brand image influences attendance intention (β=0.38). It is concluded that significant brand loyalty, coupled with strong brand image and positive brand equity explain a significant part of the intention to attend Peruvian private universities.
Keywords: Loyalty; brand image; brand equity; attendance intention; universities; Perú.